Characterizing NSAID Allergy and Strategies for Management in Patients with Rheumatological and Orthopaedic Conditions, in a Single Tertiary Hospital in Hong Kong - James Hooi; Gordon Kwok Ho Chu; Jane Chi Yan Wong; Philip Li (Journal of Clinical Rheumatology and Immunology)
Background Non-steroidal anti-inflammatory drugs (NSAIDs) are amongst the most frequently prescribed medications, their associated hypersensitivity reactions can not only lead to potentially severe reactions, but also limit analgesic and anti-inflammation options. This is especially true for those who are ailed with rheumatological or orthopaedic diseases leading to chronic pain and inflammatory conditions. This highlights the importance of identifying different types of NSAID hypersensitivity, and to find safe alternatives, namely selective COX-2 inhibitors, to groups of patients that may benefit the most from its utility. Objective To assess and categorise patients with suspected NSAID hypersensitivity, and to successfully provide alternatives to those with chronic rheumatologic and orthopedic ailments. Methods 115 patients with suspected NSAID hypersensitivity were referred to Queen Mary Hospital for specialist evaluation between Jan 2023 and March 2024, those suitable were later challenged and delabelled. Remaining patients were assessed as clinically compatible with NSAID hypersensitivity, and later separated into whether they had background of orthopedic or rheumatological conditions, hence strong indications for NSAIDs, and without, to which selective COX-2 inhibitors tolerance tests were offered. Results Of 115 patients, 20% (23/115) were assessed as unlikely to have NSAID hypersensitivity, and later challenged. 18.2% (21/115) had negative challenges and were delabelled; only 2 patients had positive reactions, confirming NSAID hypersensitivity, of which symptoms were mild and did not require hospitalization. 82% of the remaining patients (94/115) were then later stratified into different NSAID hypersensitivity reactions according to European Academy of Allergy & Clinical Immunology (EAACI) guidelines. 57.3% (66/115) of patients were able to resume use of NSAIDs either by finding an alternative NSAID, namely a selective COX2 inhibitor (45/115, 39.1%), or through a negative drug challenge (21/115, 18.2%). Overall there was no significant difference in the proportion of patients with successful COX2 inhibitor challenges between the group with rheumatological and orthopedic diagnoses against those without (62% vs 54% p=0.414). 29 patients are still pending workup, likely underestimating the amount of patients that are able to resume NSAIDs. Conclusion NSAID hypersensitivity is amongst the most commonly reported drug allergies, and may present with many different clinical phenotypes. Patients with suspected NSAID hypersensitivity require allergist evaluation, and if not clinically suggestive of allergy, would benefit from drug challenges, especially in cases with underlying rheumatological or orthopedic conditions, where NSAIDs are essential. In situations where NSAID hypersensitivity is considered likely, selective COX-2 inhibitors can often be considered as a suitable alternative.